Classificação de sites a partir das análises estrutural e textual - Ribas, Oeslei Taborda (2013)
With the wide use of the web nowadays, also with its constant growth, task of automatic classification of websites has gained increasing importance. In many occasions it is necessary to block access to specific sites, such as in the case of access to adult content sites in elementary and secondary schools. In the literature different studies has appeared proposing new methods for classification of sites, with the goal of increasing the rate of pages correctly categorized. This work aims to contribute to the current methods of classification by comparing four aspects involved in the classification process: classification algorithms, dimensionality (amount of selected attributes), attributes evaluation metrics and selection of textual and structural attributes present in webpages. We use the vector model to treat text and an machine learning classical approach according to the classification task. Several metrics are used to make the selection of the most relevant terms, and classification algorithms from different paradigms are compared: probabilistic (Na¨ıve Bayes), decision tree (C4.5), instance-based learning (KNN - K-Nearest Neighbor) and support vector machine (SVM). The experiments were performed on a dataset containing two languages, English and Portuguese. The results show that it is possible to obtain a classifier with good success indexes using only the information from the anchor text in hyperlinks, in the experiments the classifier based on this information achieved 99.59% F-measure.